LEADER-MEMBER EXCHANGE AND PERCEIVED ORGANIZATIONAL SUPPORT ON INNOVATIVE WORK BEHAVIOR : MEDIATING ROLES OF SELF-EFFICACY - Khauliyah Liyana; Jufrizen; Bahril Datuk (RADJA PUBLIKA, 2024)
This research investigates the impact of Leader-Member Exchange (LMX) and Perceived Organizational Support (POS) on Innovative Work Behavior (IWB), with self-efficacy acting as a mediator. Utilizing a causal approach and drawing on human resource management theories, the study targeted all employees of PT Sabas Indonesia. A representative sample of fifty employees was selected to provide comprehensive insights. Data collection methods included detailed documentation, systematic observation, and structured questionnaires, ensuring robust data gathering. Quantitative data analysis was conducted using the Partial Least Square (PLS) software, known for its efficiency in handling complex models. The findings indicate that both LMX and POS significantly influence IWB, highlighting the importance of supportive and effective leader-member interactions and organizational backing. Additionally, LMX and POS were found to have a notable impact on self-efficacy, which in turn mediates the relationship between POS, indirect LMX, and IWB. These results underscore the critical role of self-efficacy in enhancing innovative behaviors in the workplace.